"See Me, See Us": Understanding the Intersections and Continued Marginalization of Adolescent Gifted Black Girls in U.S. Classrooms. Issue 2 (April 2020) - Anderson, Brittany N.
In current research and theoretical models that address racial inequity or gender disparities in gifted education, there is a missing narrative around high-achieving/gifted Black girls and their experiences, as well as their disproportionate underrepresentation in gifted programming, services, and Advanced Placement (AP) courses. This article highlights literature on adolescent gifted Black girls, in addition to exploring barriers and issues of marginalization that constrain the talent identification and development of this population. The study explores the narratives of gifted Black women and explores their counternarratives using Critical Race Theory and Frasier's Talent Assessment Profile (F-TAP) framework. The article urges educators to use an intersectional lens to understand and address the needs of adolescent gifted Black girls, and provides practical tools to identify and develop talent.